In-depth Sampling of High-risk Populations to Characterize HIV Transmission Epidemics Among Young MSM Using PrEP in France and Quebec. (15th February 2019) - Chaillon, Antoine; Delaugerre, Constance; Brenner, Bluma; Armero, Alix; Capitant, Catherine; Nere, Marie Laure; Leturque, Nicolas; Pialoux, Gilles; Cua, Eric; Tremblay, Cecile; Smith, Davey M; Goujard, Cecile; et al.
Abstract: Background: A better understanding of HIV transmission dynamics among populations at high risk is important for development of prevention strategies. We determined HIV transmission networks from infected individuals enrolled in the pre-exposure prophylaxis (PrEP) IPERGAY trial in combination with the ANRS PRIMO and Montreal PHI cohorts to identify and characterize active clusters of transmission in this high-risk population. Methods: Genotypic resistance tests were performed on plasma samples from 31 IPERGAY participants. Reverse transcriptase sequences were analyzed in combination with unique HIV pol sequences from 1351 individuals enrolled in the PRIMO ANRS cohort (1999–2014) and 511 individuals enrolled in the Montreal PHI cohort (1996–2016). Network analyses were performed to infer putative relationships between all participants. Results: Overall, 1893 participants were included. Transmission network analyses revealed that 14 individuals (45.2%) from the IPERGAY trial were involved in 13 clusters sampled over a median period (interquartile range) of 2 (0.3–7.8) years, including 7 dyads and 6 larger clusters ranging from 4 to 28 individuals. When comparing characteristics between clustering individuals enrolled in the PRIMO cohort (n = 377) and in IPERGAY (n = 14), we found that IPERGAY participants had a higher viral load (5.93 vs 5.20 log10 copies/mL, P = .032) and reported a higher number of partners in the last 2 months ( P < .01). Conclusions: These results demonstrate high rates of HIV transmission clustering among young high-risk MSM enrolled in the IPERGAY trial. In-depth sampling of high-risk populations may help to uncover unobserved transmission intermediaries and improve prevention efforts that could be targeted to the most active clusters.